IDENTIFICATION OF A PUTATIVE MEMBRANE-INSERTED SEGMENT IN THE ALPHA-TOXIN OF STAPHYLOCOCCUS-AUREUS - Ward, R. J.; Palmer, M.; Leonard, K.; Bhakdi, S. (Amer Chemical Soc, 1994)
To gain a fuller understanding of the regions of the Staphylococcus aureus alpha-toxin important in pore formation, we have used Forster dipole-dipole energy transfer to demonstrate that a central glycine-rich region of alpha-toxin (the so-called ''hinge'' region) inserts deeply into the bilayer on association of toxin with liposomes. Mutant alpha-toxins with unique cysteine (C) residues at positions 69 and 130 [Palmer, M., et al. (1993) J. Biol. Chem. 268, 11959) were reacted with the C-specific fluorophore acrylodan, which acted as an energy donor. The chosen acceptor was N-(7-nitrobenz-2-oxa-13-diazol-4-yl)-1,2-bis(hexadecanoyl) -sn-glycero-3-phosphoethanolamine (NBD-PE). Measurement of the degree of donor quenching with increasing NBD-PE in the inner bilayer leaflet enables the distance of closest approach between donor and acceptor to be estimated. For toxin labeled with acrylodan at position 130 (in the hinge region), this distance is approximately 5 +/- 2 Angstrom, showing that the probe is close to the inner surface of the liposomes. A second probe labeled at position 69 (in the N-terminal domain) shows negligible energy transfer, indicating a distance of closest approach >40 Angstrom. This implies that this N-terminal region remains ''outside'' the liposome. We propose a model in which the central region of the alpha-toxin inserts into the membrane and possibly participates in forming the wall of the pore.